Pengaruh Kualitas Produk, Citra Merek dan Harga Terhadap Keputusan Pembelian Roti Mako Cake And Bakery Jatinangor Town Square - Ahmad Hisam Umar; Pemilia Sulistyowati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of product quality, brand image, and price on consumer purchase decisions at Mako Cake and Bakery Jatinangor Town Square. A quantitative approach using a survey method was applied. A total of 100 respondents were selected using accidental sampling. Data were collected through questionnaires and analyzed using multiple linear regression in SPSS. The results showed that product quality, brand image, and price significantly influence purchase decisions both partially and simultaneously. These findings indicate that all three variables play a vital role in shaping consumer decisions and should be considered in marketing strategies.